Analisis Dampak Air Lindi Terhadap Kualitas Air Sumur Di Sekitar Tempat Pembuangan Akhir Tibar, Kabupaten Liquiçá, Timor-Leste - Osvaldo Vong Ximenes Gama; Winarti Winarti; Agung Dwi Sutrisno (Riviera Publishing, 2025)
Leachate from the Waste Disposal Site (WDS) poses a risk of seeping into the ground and contaminating community well water. This study was conducted to examine the impact of WDS effluent on the water quality of wells in Tibar Village, Liquiçá Regency, Timor-Leste, and to evaluate the correlation between well proximity and the degree of contamination. The research employed a descriptive-analytic methodology with a quantitative approach, involving twelve well sites situated near the WDS. Water quality was assessed through analysis of physical parameters (pH, turbidity, TDS, conductivity, salinity), chemical parameters (ammonia, magnesium, nitrate, nitrite, calcium, manganese), and microbiological parameters (total coliform, Escherichia coli). The test results indicated that several parameters exceeded Timor Leste National Laboratory Agency, including ammonia up to 0.99 mg/L, magnesium at 102.6 mg/L, calcium at 168 mg/L, TDS at 1,384 mg/L, conductivity at 2,710 µS/cm, salinity at 1.40 ppt, and total coliform at 4 MPN/100 mL. Elevated concentrations were predominantly observed in wells located within 500 meters of the WDS, suggesting the infiltration of Leachate into the groundwater. These findings highlight a relationship between the proximity of wells to the WDS and the high levels of contamination, underscoring the need for enhanced waste management practices, regular water quality monitoring, and water source protection policies to safeguard public health.